VALIDITY OF PRE-ISLAMIC ARABIC LITERATURE AS A SOURCE OF AUTHENTICATION OF HADIS - Mochammad Achwan Baharuddin; Moh. Erfan Soebahar; Siti Mujibatun (UIN Sunan Kalijaga Yogyakarta, 2020)
The focus of this paper is the authenticity of the hadith, because in addition to the problem of the method used, it is also a matter of sources that are problematic. One source that is often used is literature, especially pre-Islamic Arabic literature (jahiliyah). The relevance of literature in authenticating hadith gives rise to a question, the extent to which the validity of pre-Islamic Arabic Literature can be used as evidence and what are the requirements that must be met when the study of the authenticity of hadith uses pre-Islamic Literature as one of the proofs. Using a Using a descriptive analytic method with a historical approach, this paper concludes that pre-Islamic Arabic literature when used as a source of authenticity of the hadith then the task of research is to reduce the difference in question. The reduction is intended so that the legality of literature as a source of hadith authentication can be accepted. This reduction includes: (1) authorship. Just as the news attributed to the Prophet must be proven to have its source in the Prophet, pre-Islamic Arabic Literature must also be proven to come from pre-Islamic Arabic writers, (2) narration. Pre-Islamic Arabic literature must also be tested extrinsically as an extrinsic factor test on the Hadith of the Prophet, (3) context. Literature was born not in an empty space so that the content of pre-Islamic Arabic literature must also reflect the life of the Arab Nation in pre-Islamic times. Therefore, when the reduction has not yet been carried out, in the context of the accuracy of the study of the authenticity of the hadith it cannot be accepted.